2000
DOI: 10.1046/j.1365-2222.2000.00845.x
|View full text |Cite
|
Sign up to set email alerts
|

Der p 1 and Der f 1, the highly related and major allergens from house dust mites, are differentially affected by a plant cystatin

Abstract: Der p 1 and Der f 1 behave very differently towards a plant cystatin, thus indicating substantial differences in their proteolytic activity. This fact could be significant with regards to the immunogenic properties of both allergens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Moreover, many other studies have shown that PhyCys also affect the growth or survival of other inseets, nematodes and slugs on artificial diets or delivered through transgenic plants (Walker et al 1999;Lilley et al 2004;Ribeiro et al 2006;Konrad et al 2009;Carrillo et al 2010). In contrast, the anti-mite properties of cystatins have only been proven using the chestnut cystatin against house dust mite species (Pernas et al 2000). In this context, the aim of the present study was to assess the putative acaricide effeets of the whole barley gene cystatin family against two phytophagous mites, T. urticae and B. chilensis, with impact on agricultural crops and to select the best cystatin as trangene to study its in vivo impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, many other studies have shown that PhyCys also affect the growth or survival of other inseets, nematodes and slugs on artificial diets or delivered through transgenic plants (Walker et al 1999;Lilley et al 2004;Ribeiro et al 2006;Konrad et al 2009;Carrillo et al 2010). In contrast, the anti-mite properties of cystatins have only been proven using the chestnut cystatin against house dust mite species (Pernas et al 2000). In this context, the aim of the present study was to assess the putative acaricide effeets of the whole barley gene cystatin family against two phytophagous mites, T. urticae and B. chilensis, with impact on agricultural crops and to select the best cystatin as trangene to study its in vivo impact.…”
Section: Discussionmentioning
confidence: 99%
“…Deleterious effects against phytopathogenic fungi and virases have also been described for these inhibitors (Gutiérrez-Campos et al 1999;Martinez et al 2003;Abraham et al 2006). To the best of our knowledge, there is only a reference showing the acaricide properties of a phytocystatin, the CsC cystatin from chestnut (Pernas et al 2000). The CsC inhibited the crude digestive protease activity of the house dust mite Dermatophagoides farinae and drastically increased the mite larval mortality when was added to a semisynthetic diet.…”
Section: Introductionmentioning
confidence: 99%
“…The defense role has been inferred from the ability of PhyCys to inhibit digestive proteinases from herbivorous arthropods in vitro, in artificial diets as well as by bioassays on transgenic plants over-expressing PhyCys genes (Pernas et al 1998;Á lvarez-Alfageme et al 2007). Anti-mite activities and deleterious effects against phytopathogenic fungi and viruses have also been described for these inhibitors (Gutierrez-Campos et al 1999;Pernas et al 2000;Martinez et al 2003;Abraham et al 2006).…”
Section: [Lvi]-[agt]-[rke]-[fy]-[as]-[vi]-x-mentioning
confidence: 99%
“…The defense function has been inferred from the ability of PhyCys to inhibit the activity of digestive proteases from arthropods in vitro, in artificial diets as well as through bioassays on transgenic plants overexpressing PhyCys genes (Pernas et al, 1998;Atkinson et al, 2004;Ribeiro et al, 2006;Alvarez-Alfageme et al, 2007). Anti-mite activities and deleterious effects against phytopathogenic fungi and viruses have also been described for these inhibitors (Gutierrez-Campos et al, 1999;Pernas et al, 2000;Martinez et al, 2003;Abraham et al, 2006;Wang et al, 2008).…”
Section: ([Lvi]-[agt]-[rke]-[fy]-[as]-[vi]-x-[edqv]-mentioning
confidence: 99%